A campanha operário padrão : como tornar-se um modelo de trabalhador (1970-1985) - Campos, Daniela de (2014)
This paper aims to discuss the Campaign Operario Padrao in the period 1970-1985. To this end, we used documents related to the contest; especially of workers who won the competition in the state of Rio Grande do Sul at the mentioned period, as well as oral interviews with some of these personages. The contest, held since 1955 in the state of Rio de Janeiro and then extended to the rest of the country, lasted for a long time, until the late 1980s. When created, according to its initiators, had the goal to spread a positive image of the Brazilian worker, contrary to what was published regularly in newspapers. The campaign, sponsored by SESI and the newspaper O Globo, proposed awarding a worker in each state, and then elect a national worker. The research examines how the competition was used by businessmen, through SESI, to propagate the ideals of harmony between the classes, creating a model worker which was in line with the standards of the Brazilian business elite and which had as a goal to discipline through the model, the remaining factories workers.